Chemicals with increasingly complex modes of action result in greater variation in sensitivity between earthworm species. (1st March 2021) - Robinson, Alex; Lahive, Elma; Short, Stephen; Carter, Heather; Sleep, Darren; Pereira, Gloria; Kille, Peter; Spurgeon, David
Abstract: The scale of variation in species sensitivity to toxicants has been theoretically linked to mode of action. Specifically, it has been proposed there will be greater variations for chemicals with a putative specific biological target than for toxicants with a non-specific narcotic mechanism. Here we test the hypothesis that mode of action is related to variation in sensitivity in a specifically designed experiment for species from a single ecologically important terrestrial taxa, namely earthworms. Earthworm toxicity tests were conducted with five species for four chemicals, providing a series of increasingly complex modes of action: a putative narcotic polycyclic aromatic hydrocarbon (fluoranthene), and three insecticides (chlorpyrifos, cypermethrin, imidacloprid) with known neuronal receptor targets. Across all the chemicals, the standard epigeic test species Eisenia fetida and Lumbricus rubellus, were generally among the two least sensitive, while the endogenic Aporrectodea caliginosa and Megascolecidae Amynthas gracilis were generally more sensitive (never being among the two least sensitive species). This indicates a potential for bias in the earthworm ecotoxicology literature, which is dominated by studies in epigeic Lumbricidae, but contains few endogeic or Megascolecidae data. Results confirmed the lowest range of variation in sensitivities for effects on reproduction was for fluoranthene (2.5 fold). All insecticides showed greater variation for species sensitivity (cypermethrin: 7.5 fold, chlorpyrifos: 10.3 fold, imidacloprid: 31.5 fold) consistent with the specific mechanisms of the pesticides. Difference in toxicodynamics, based on mode of action specificity and receptor complexity was reflected in the magnitude of sensitivity variation. However, measurements of tissue concentrations also indicated the potential importance of toxicokinetics in explaining species sensitivity variations for chlorpyrifos and cypermethrin. Graphical abstract: Image 1 Highlights: Earthworm toxicity tests were conducted with five species. Toxicity for 3 insecticides greater than for a PAH in all species. Greater variation in sensitivity between species for insecticides than for a PAH. Species tissue chlorpyrifos, cypermethrin, fluoranthene reflects sensitivity. No relationship of the ordering of tissue imidacloprid with sensitivity. Abstract : Earthworm species sensitivity varies more widely for three specifically acting insecticides than for a non-specifically acting PAH.